Commute UX: Telephone Dialog System for Location-based Services - Tashev, Ivan; Seltzer, Mike; Yu, Dong; Acero, Alex; Ju, Y. C. (Proceedings of SIGdial Workshop on Disclosure and Dialogue 2007, 2007)
In this paper, we describe a telephone dialog system for location-based services. In such systems, the effectiveness with which both the user can input location information to the system and the system delivers location information to the user is critical. We describe strategies for both of these issues in the context of a dialog system for real-time information about traffic, gas prices, and weather. The strategies employed by our system were evaluated through user studies and a system employing the best strategies was deployed. The system is evaluated through an analysis of 700 calls over a two month period.